On the molecular basis of D-bifunctional protein deficiency type III. - Maija L Mehtälä; Marc F Lensink; Laura P Pietikäinen; J Kalervo Hiltunen; Tuomo Glumoff (PLoS ONE, 2013)
Molecular basis of D-bifunctional protein (D-BP) deficiency was studied with wild type and five disease-causing variants of 3R-hydroxyacyl-CoA dehydrogenase fragment of the human MFE-2 (multifunctional enzyme type 2) protein. Complementation analysis in vivo in yeast and in vitro enzyme kinetic and stability determinants as well as in silico stability and structural fluctuation calculations were correlated with clinical data of known patients. Despite variations not affecting the catalytic residues, enzyme kinetic performance (K(m), V(max) and k(cat)) of the recombinant protein variants were compromised to a varying extent and this can be judged as the direct molecular cause for D-BP deficiency. Protein stability plays an additional role in producing non-functionality of MFE-2 in case structural variations affect cofactor or substrate binding sites. Structure-function considerations of the variant proteins matched well with the available data of the patients.